Effect of lattice misfit on the evolution of the dislocation structure in Ni-based single crystal superalloys during thermal exposure. (November 2016) - Long, Haibo; Wei, Hua; Liu, Yinong; Mao, Shengcheng; Zhang, Jianxin; Xiang, Sisi; Chen, Yanhui; Gui, Weimin; Li, Qing; Zhang, Ze; Han, Xiaodong
Abstract: In this study, we investigate the movement of dislocations in Ni-based superalloys under the influence of lattice misfit stresses between the ordered γ'-cuboids and the disordered γ-matrix during thermal exposure in the absence of an applied load. This study focuses on a different condition than the conventional creep testing, and thus offers a unique opportunity to study the intrinsic behavior of the alloy. The dislocation density increases substantially with time during thermal exposure, leading to the formation of various configurations of dislocation networks on the 100γ/γ′ interfaces, including <110> diamond-shaped, <110>/<100> mixed polygon-shaped and <100> square-shaped networks. During thermal exposure, the b = 1 2 < 110 > native dislocations first move and evolve into 60° mixed dislocations along the <110> directions on the 100γ/γ′ interfaces, forming the <110> diamond-shaped dislocation networks. In the case of longer thermal exposures, the dislocations further evolve into pure edge dislocations along the <100> on the 100γ/γ′ interface, leading to the evolution of the <110> diamond-shaped dislocation networks into <100> square-shaped networks, with the mixed <110>/<100> dislocation networks as an intermediate stage during the transition. These movements occur by sweep glide in the 111 planes and diagonal climb on the 100 planes for the edge and mixed dislocations and by cross-slip for the screw dislocations. The driving force for all of these movements is the interaction between the normal misfit stresses and the edge components of the Burgers vectors of the dislocations to relax the misfit stresses. An analysis based on the elastic strain energy considerations is presented to explain the driving forces for the dislocation movements. Graphical abstract: